Antileishmanial activity of amphiphilic chlorin derivatives mediated by photodynamic therapy - Linares, Irwin A.P.; Velásquez, Angela M.A. [UNESP]; Graminha, Marcia A.S. [UNESP]; de Oliveira, Kleber T.; Perussi, Janice Rodrigues (Elsevier, 2020)
Leishmaniasis is a serious and neglected disease that affects 14 million people around the World. The currently available drugs for treatment present several drawbacks such as low efficacy and severe side effects, contributing to patients’ low compliance. Photodynamic therapy (PDT) is rising as a promising treatment of cutaneous leishmaniasis, mainly considering its topical administration that circumvents any potential adverse effects commonly related to oral/parenteral administration. PDT depends on the interaction between a light-sensitive compound (photosensitizer - PS), light and molecular oxygen. The reaction generates reactive oxygen species (ROS) which induce cell death by oxidative stress. The main goal of this study is to demonstrate the antileishmanial effect of three chlorin derivatives (CHL-OH-A, CHL-OH-B, CHL-TRISMA) using PDT, as well as to investigate their cell death pathway on Leishmania amazonensis promastigote forms after chlorin-PDT application. The chlorin derivatives herein studied did not exhibit aggregates in aqueous medium and showed fast accumulation in Leishmania acidic compartments. CHL-OH-A exhibited the highest antiparasitic activity at 24 h (0.33 μmol L−1) and 48 h (0.14 μmol L−1) after irradiation at 660 nm (6.0 Jcm-2). CHL-OH-A, CHL-OH-B and CHL-TRISMA molecules induced the cell death of parasites mainly by an apoptotic-like process in the presence of light. These chlorin derivatives are 80-fold more active against Leishmania when compared to other PSs reported in the literature. In this study, we have shown that these amphiphilic chlorins, and in particular, CHL-OH-A, exert an interesting leishmanicidal activity suggesting that the use of these PSs associated with PDT could be a promising strategy for treatment of cutaneous leishmaniasis.
Keywords: Cell death; Chlorin derivatives; Leishmania acidic compartments; Leishmania amazonensis; Photodynamic therapy; Photosensitizer